Α7 nicotinic acetylcholine receptors in the hippocampal circuit: taming complexity. Issue 2 (February 2022) - Letsinger, Ayland C.; Gu, Zhenglin; Yakel, Jerrel L.
Abstract : Cholinergic innervation of the hippocampus uses the neurotransmitter acetylcholine (ACh) to coordinate neuronal circuit activity while simultaneously influencing the function of non-neuronal cell types. The α7 nicotinic ACh receptor (nAChR) subtype is highly expressed throughout the hippocampus, has the highest calcium permeability compared with other subtypes of nAChRs, and is of high therapeutic interest due to its association with a variety of neurological disorders and neurodegenerative diseases. In this review, we synthesize research describing α7 nAChR properties, function, and relationship to cognitive dysfunction within the hippocampal circuit and highlight approaches to help improve therapeutic development. Highlights: α7 nAChR expression is abundant in the hippocampus and located pre- and postsynaptically in most neuronal types as well as in non-neuronal cells such as astrocytes, microglia, macrophages, and endothelial cells. α7 nAChRs have low affinity for acetylcholine (EC50 180 μM), indicating that they are likely coactivated with other cholinergic receptor subtypes. Timing of α7 nAChR activation related to excitatory inputs alters the effect on postsynaptic plasticity, influencing theta oscillations. A single basal forebrain cholinergic neuron can innervate cells in all layers of the hippocampus, possibly coordinating hippocampal activities. Therapies for α7 nAChR-related dysfunction should preserve the function of cholinergic projection neurons and/or utilize modulators that enhance function while preserving response kinetics to maintain the circuit's temporal fidelity.